Parallel diversifications of Cremastosperma and Mosannona (Annonaceae), tropical rainforest trees tracking Neogene upheaval of South America. Issue 1 (31st January 2018) - Pirie, Michael D.; Maas, Paul J. M.; Wilschut, Rutger A.; Melchers-Sharrott, Heleen; Chatrou, Lars W.
Abstract : Much of the immense present day biological diversity of Neotropical rainforests originated from the Miocene onwards, a period of geological and ecological upheaval in South America. We assess the impact of the Andean orogeny, drainage of Lake Pebas and closure of the Panama isthmus on two clades of tropical trees ( Cremastosperma, ca 31 spp.; and Mosannona, ca 14 spp.; both Annonaceae). Phylogenetic inference revealed similar patterns of geographically restricted clades and molecular dating showed diversifications in the different areas occurred in parallel, with timing consistent with Andean vicariance and Central American geodispersal. Ecological niche modelling approaches show phylogenetically conserved niche differentiation, particularly within Cremastosperma . Niche similarity and recent common ancestry of Amazon and Guianan Mosannona species contrast with dissimilar niches and more distant ancestry of Amazon, Venezuelan and Guianan species of Cremastosperma, suggesting that this element of the similar patterns of disjunct distributions in the two genera is instead a biogeographic parallelism, with differing origins. The results provide further independent evidence for the importance of the Andean orogeny, the drainage of Lake Pebas, and the formation of links between South and Central America in the evolutionary history of Neotropical lowland rainforest trees.